REDESCRIPTION OF Tarsubulura perarmata (RATZEL, 1868) FROM A WILD-CAUGHT EASTERN TARSIER (Tarsius sp.) - Endang Purwaningsih; Lily Endang Setyorini; Myron Shekelle (Treubia, 2004)
Tarsubulura perarmata (Rai zel, 1868) is rcdescribed on tile basis of specimens [roin the intestine of tuild caught Tarsius sp. The specimens were compared with original description of Subulura perarmata, Ratzel, 1868 and the description by Brack and Niemitz, 1984. Inglish (1958) transferred this species to Tarsubulura perarmata and a redescription of this taxon is presented in this paper.